Manusia Sebagai Instrumen Dalam Perlawanan Antara Allah dan Iblis: Penelurusan Narasi Ayub 1-2 - Musa sandrianto (Institut Agama Kristen Negeri Toraja, 2020)
The book of Job chapters 1-2 contains a narrative of resistance between God and the Devil. Interestingly, in the narration of Job chapters 1-2 the resistance between God and Satan uses humans (Job) as his instrument. The question is what is man's goal as an instrument in the struggle between God and Satan? How does God use humans (Job) as an instrument in His fight with Satan? The purpose of this study is to find out what God's purpose is to use humans (Job) as an instrument against Satan. This writing uses a qualitative method with the type of narrative approach to the book of Job chapters 1-2. The use of narrative descriptions is very important to see the fierce resistance between God and Satan, where humans (Job) are the instruments. The findings in the study are (1) God is sovereign to use everyone including Job for his purposes. (2) In the narrative study of Job chapters 1 and 2 it is found that all the actions of Satan are under God's supervision and will. Without God's permission, Satan cannot do anything. (3) All actions of creation including Satan are in the sovereignty of God.Kitab Ayub pasal 1-2 terdapat narasi perlawanan antara Allah dan Iblis. Menariknya dalam narasi Ayub pasal 1-2 perlawanan antara Allah dan Iblis memakai manusia (Ayub) sebagai instrumennya. Pertanyaannya adalah apa tujuan manusia sebagai instrumen dalam perlawanan antara Allah dan Iblis? Bagaimana Allah memakai manusia (Ayub) sebagai instrumen dalam perlawanan -Nya dengan Iblis? Tujuan dari penelitian ini, untuk mengetahui apa maksud Allah memakai manusia (Ayub) sebagai instrument dalam melawan Iblis. Penulisan ini menggunakan metode kualitatif dengan jenis pendekatan narasi terhadap kitab Ayub pasal 1-2. Penggunaan Narasi deskripsi ini sangat penting untuk melihat perlawanan sengit antara Allah dan Iblis di mana manusia (Ayub) sebagai instrumennya. temuan-temuan dalam penelitian adalah (1) Allah berdaulat memakai setiap orang termasuk Ayub untuk maksud dan tujuannya. (2) Dalam kajian narasi Ayub pasal 1 dan 2 ditemukan bahwa segala tindakan Iblis ada dalam pengawasan dan kehendak Tuhan. Tanpa seizin Tuhan, Iblis tidak dapat berbuat apa-apa. (3) Segala tindakan ciptaan termasuk Iblis ada dalam kedaulatan Allah.